A Descriptive Study of English Speaking Anxiety and Teaching Strategies among 11th Grade Language Students at SMA Negeri 1 Payangan - Dwi Septiani (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2026)
This study investigates the causes of English speaking anxiety and explores teaching strategies that help reduce such anxiety among eleventh-grade language students at SMA Negeri 1 Payangan. Employing a descriptive quantitative approach, data were collected from 30 participants through a structured questionnaire focusing on both anxiety indicators and students’ perceptions of classroom strategies. The findings reveal that a significant number of students experience moderate to high levels of anxiety, particularly related to fear of making mistakes, peer judgment, and forgetfulness during speaking tasks. Descriptive statistical analysis showed that physical symptoms such as a racing heartbeat and emotional barriers like embarrassment were prevalent. The study also identified several effective teaching strategies for reducing anxiety, including teacher encouragement, role-play activities, group discussions, and a relaxed classroom atmosphere. Among these, role-play was perceived as the most engaging and impactful. The results highlight the importance of supportive, interactive, and student-centered pedagogical approaches in fostering confidence and improving speaking performance in EFL contexts.